Genome editing in macroalgae: advances and challenges - De Saeger, Jonas; Coulembier Vandelannoote, Emma; Lee, Hojun; Park, Jihae; Blomme, Jonas (Frontiers in Genome Editing, 2024)
This minireview examines the current state and challenges of genome editing in macroalgae. Despite the ecological and economic significance of this group of organisms, genome editing has seen limited applications. While CRISPR functionality has been established in two brown (Ectocarpus species 7 and Saccharina japonica) and one green seaweed (Ulva prolifera), these studies are limited to proofof-concept demonstrations. All studies also (co)-targeted ADENINE PHOSPHORIBOSYL TRANSFERASE (APT) to enrich for mutants, due to the relatively low editing efficiencies. To advance the field, there should be a focus on advancing auxiliary technologies, particularly stable transformation, so that novel editing reagents can be screened for their efficiency. More work is also needed on understanding DNA repair in these organisms, as this is tightly linked with the editing outcomes. Developing efficient genome editing tools for macroalgae will unlock the ability to characterize their genes, which is largely uncharted terrain. Moreover, given their economic importance, genome editing will also impact breeding campaigns to develop strains that have better yields, produce more commercially valuable compounds, and show improved resilience to the impacts of global change.